A política de fundos constitucionais no contexto do financiamento da educação básica no Brasil : origens, contradições e perspectivas - JESUS, Wellington Ferreira de (2011)
This study integrates the research about State and Public Education Policies in Brazil. Its aim is to analyze the historical origins, the context, the relevance and the contradictions, limitations and possibilities of linking, mainly of funds policy, also called funds sublinkings, in the context of the financing of basic education. In this sense, we conducted an initial historical research in documentary sources, such as: proceedings diaries of the constituent assemblies, National Congress journals, Official Gazette, brazilian constitutions and other official documents; national and regional newspapers, sites of the computers world wide network, among others. There was a literature review as well, whose objective was to contextualize the linkings and sublinkings, situating them in the context of a pendulous movement, consolidated during the democratic State and abolished in the exception regimes. Therefore, taking the theory of Antonio Gramsci on the Expanded State as a reference, the role of linking and educational funds policy to education was discussed, in view of another planning on this kind of policy in Brazil. It was noticed that constitucional funds policy represents, among other things, a mechanism that enables the fulfilment of management, projects, policies, and, especially of a community participation in control, monitoring and auditing of funds allocated to the educational sector. In this sense, the roles of Fundef and Fundeb were contextualized and discussed as concrete experiences of development of linkings. It was found, in relation to Fundef, created in 1997 in the management of the president Fernando Henrique Cardoso, the dimension of the political focus, limited itself by reforms and structural adjustments that, in the context of neoliberalism, privileged elementary education. In Fundeb, created in 2007 in the management of the president Luís Ignácio Lula da Silva, it was observed an increase in the scope of the school population attended, expanding the destination to basic education. However, it was noticed that about the fundamental aspects − complementation of the Union, the value per student and per year, appreciation of teaching, among others − both funds were inferior to the real needs of the education sector. A process of enrollments expanding and a definition of the subnational governments role were found. Meanwhile, due to a deregulation in the collaboration system, as it was determined by the Brazilian Constitution of 1988, it still remains an overload among the federal units in Brazilian municipalities. The contradictions in Fundef and Fundeb were object of study and preparation of reports, surveys, impact analysis, debates and laws approved by the legislature, which resulted in a historic accumulation. The existence of an effective system of collaboration, establishmentof the cost-student-quality, participation of society in the advisory concils and social control, presence of the representation of Public Ministry as well as the appreciation of teaching may result in an improvement in the dynamics of the education financing in Brazil, at the end of this study. Thereby, such improvements will contribute significantly to the overcoming of inequalities and ensure of the materiality of the right to free and public education as a social right.